Le Songe De Vaux - Young, Carolin C (Petits Propos Culinaires, 2001)
This paper was delivered to the Oxford Symposium on Food & Cookery in September 2000. The article provides an account of the magnificent banquet hosted by Nicolas Fouquet at his recently completed chateau, Vaux-le-Vicomte in 1661. Within 3 weeks the host was arrested for treason by Louis XIV, a guest at the banquet whose future efforts at Versailles, the author speculates, must have been influenced by Fouquet's example.